2003
DOI: 10.1037/0002-9432.73.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder in adopted children from Romania.

Abstract: This follow-up study of 80 Romanian children showed that 16 (20%) of the children exhibited posttraumatic stress disorder (PTSD). The same children got scores in the clinical range on the Child Behavior Checklist (CBCL). These PTSD children could be differentiated from the remaining children by psychosocial but not by physical health variables. Children showing characteristics of PTSD stood out from the other subjects because of their scores on the Externalization dimension and excessive attention-seeking on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…The theoretical basis of the interventions reviewed to date has been cognitive-behavioural and the format has been a skills-based approach. However, the fostered/adopted population of children is different from children residing with their biological parents due to the prevalence of trauma symptomology (Hoksbergen et al, 2003;Oswald et al, 2010) and therefore it has been argued that these interventions alone should not be expected to impact as positively in this more complex population (Hodges, 2005).…”
Section: Intervening Through Caregiversmentioning
confidence: 99%
“…The theoretical basis of the interventions reviewed to date has been cognitive-behavioural and the format has been a skills-based approach. However, the fostered/adopted population of children is different from children residing with their biological parents due to the prevalence of trauma symptomology (Hoksbergen et al, 2003;Oswald et al, 2010) and therefore it has been argued that these interventions alone should not be expected to impact as positively in this more complex population (Hodges, 2005).…”
Section: Intervening Through Caregiversmentioning
confidence: 99%
“…Turkish youths exposed to an earthquake have also shown severe or very severe levels of PTSD (Bal and Jensen 2007). Hoksbergen et al (2003) examined 80 children adopted from Romania into the Netherlands and found that 20.0% of boys and girls demonstrated clinical PTSD. A comparison with youths without PTSD revealed no age, health, or family differences but youths with PTSD did show many more behavioral problems listed on the Child Behavior Checklist.…”
Section: Ptsd and Maltreatment: Epidemiologymentioning
confidence: 99%
“…(Hoksbergen & Walenkamp, 1983;1991;Sorgedrager, 1988;Verhulst, Althaus, & Versluis-den Bieman, 1992). In addition, specific behavioral consequences have been studied, such as Reactive Attachment Disorder (Hoksbergen, 1998;O'Connor, Rutter, & The English and Romanian Adoptees Study Team, 1999); Post Traumatic Stress Disorder (Hoksbergen, 1996(Hoksbergen, , 2001Hoksbergen et al, 2003;Verrier, 1993) and Attention Deficit Hyperactivity Disorder (Hoksbergen, 1999).…”
Section: Introduction Early Child Deprivation and Post-institutional mentioning
confidence: 99%